Predictable increase of the impact of the economic crisis on public libraries during 2012 - Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2012)
The increased impact of the economic crisis on public libraries in Spain is described. The aim is to draw attention to the problems that will arise by 2012 in library services, staff, collections, and cultural and educational programs. The policy of deficit reduction and budget control will cause deep cuts in public investment in libraries. It is important to analyze this topic and see how to address it because public libraries are now more necessary than ever to meet the information needs of disadvantaged people.